Zarządzanie globalne poprzez kształtowanie wspólnot pracowników wiedzy - Morawski, Mieczysław (Global management by forming the communities of knowledge workers, 2005)
The article presents the aspect of globalization which is connected with the tendency to joining the potential of enterprises. In the conditions of New Economy, the cooperation of firms will become more and more popular. Creating the communities of professionals by knowledge workers, which go beyond seeing the organization in a traditional way, is farourable for the cooperation of enterprises. These communities create intellectual motivation, which helps to generate and use knowledge.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 65-73